Verso una teoria unificata delle arti della memoria. Antropologia, Archeologia, Psicologia cognitiva, Evoluzionistica, Neuroscienze - Guariento, Tommaso (Mechane, 2020)
This article will provide a meta-analysis of books and articles that deals (directly or selectively) with ars memoriae. In the first paragraph we consider Paolo Rossi’s invitation to extend the search field on the arts of memory; in the second paragraph we present a summary of Carlo Severi’s ethnographic studies on American mnemotechnics; in the third paragraph we will comment Lynne Kelly’s archaeological thesis; in the fourth paragraph we put Kelly’s thesis in dialogue with other archaeological insights, and with Matteo Meschiari’s Landscape Mind Theory; in the fifth paragraph we present a compendium of neuroscientific literature on reading (Dehaene), on memory and visual perception (Baddeley, Kandel) and on the areas of the brain involved in the use of the method of loci (Berthoz, Rolls). The fifth paragraph will then identify the network of cognitive structures and the areas of the brain that form the basic structure of a hypothetical ‘module for the arts of memory’. In the sixth paragraph we provide an explanation for the common narrative structure of the catabases and its connection with the arts of memory. Finally, we propose an interpretation of the birth of philosophy as an operation of questioning and reverse engineering (Brandom, Dennett) of mnemotechnic’s contents – an event that, along with the exorbitant accumulation of information caused by the invention of printing, has made the arts of memory ineffective as a tool for cultural transmission.